DETERMINAN SENJANGAN ANGGARAN - Sugianto Sugianto; Zul Azmi; Wira Ramashar (Bilancia : Jurnal Ilmiah Akuntansi, 2020)
The purpose of this study was to examine the effect of Budget Participation, Individual Capacity, Organizational Commitment, Locus of Control and Self Esteem on Budgetary Slack. The population in this study are Regional Apparatus Organization of Pekanbaru. Sample are taken by purposive sampling method. The sample of this study was 96 respondents. This study uses multiple linear regression analysis. Based on the results of the study, it can be concluded that the variables of that the variables of Budget Participation, Individual Capacity, Organizational Commitment, Locus of Control and Self Esteem affect Budgetary Slack. Tujuan dari penelitian ini adalah untuk menguji pengaruh Partisipasi Anggaran, Kapasitas Individu, Komitmen Organisasi, Locus Of Control dan Self Esteem Terhadap Senjangan Anggaran. Populasi pada peneltian ini adalah Organisasi Perangkat Daerah Kota Pekanbaru. Penarikan sampel menggunakan teknik purposive sampling. Sampel penelitian ini sebanyak 96 responden. Penelitian ini menggunakan analisis regresi linier berganda. Berdasarkan hasil penelitian, maka dapat ditarik kesimpulan bahwa variabel Partisipasi Anggaran, Kapasitas Individu, Komitmen Organisasi, Locus Of Control dan Self Esteem berpengaruh terhadap Senjangan Anggaran.